2019
DOI: 10.1590/1807-3107bor-2019.vol33.0122
|View full text |Cite
|
Sign up to set email alerts
|

Spatial inequality of dental caries in the Brazilian territory

Abstract: The distribution of harms to health varies spatially determined by the socioeconomic conditions of the environment. This research aimed to assess the spatial distribution of dental caries in 12-year-old children and their correlation with socioeconomic indicators in Brazilian states. The sample of this ecological study comprised all the 26 Brazilian states and the Federal District. Thematic and correlation maps were constructed in order to assess the spatial dependency, as well as the correlation between denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
(17 reference statements)
2
8
0
1
Order By: Relevance
“…Conceptually, individual and area socioeconomic characteristics do not necessarily belong to the same constructs, and thus, they may be affecting health through diverse mechanisms [59]. Our results are aligned with prior research reports from Mexico [6,7,38] and other countries [23,25,[27][28][29][30][31] where socioeconomic inequalities have been associated to oral health indicators. Studies on dental caries inequalities in low-and middle-income countries are relatively scarce [25], and there are even fewer studies about the spatial distribution pertaining specifically to caries [29].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Conceptually, individual and area socioeconomic characteristics do not necessarily belong to the same constructs, and thus, they may be affecting health through diverse mechanisms [59]. Our results are aligned with prior research reports from Mexico [6,7,38] and other countries [23,25,[27][28][29][30][31] where socioeconomic inequalities have been associated to oral health indicators. Studies on dental caries inequalities in low-and middle-income countries are relatively scarce [25], and there are even fewer studies about the spatial distribution pertaining specifically to caries [29].…”
Section: Discussionsupporting
confidence: 87%
“…Many causes of inequalities are difficult to identify, in part because they change in relation to their social context [22]. Several studies found significant associations between lower socioeconomic status and higher risk of dental caries [23][24][25][26][27][28][29]. Social factors influence variables associated with caries through modifying living conditions of the individual; it is feasible to gain a more accurate understanding of caries distribution through examining such a relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In the present survey, higher bleeding scores were recorded in children living in the South of Italy compared to those from the Northern sections. The utilization of dental services was found to be significantly associated with better gingival health in children 47 . The lack of adequate oral hygiene habits, the higher consumption of cariogenic foods and the non-regular dental check-ups might be the main reasons associated to the poor oral heath recorded in children living in low income and high inequality areas of the Country.…”
Section: Discussionmentioning
confidence: 93%
“…The lack of adequate oral hygiene habits, the www.nature.com/scientificreports/ higher consumption of cariogenic foods and the non-regular dental check-ups might be the main reasons associated to the poor oral heath recorded in children living in low income and high inequality areas of the Country. Dental caries and socioeconomic inequalities are under scrutiny several times 2,19,30 in different age and population groups 9,18,47 but the discriminating factors leading and linked to different stages of the disease are still unclear. In toddlers and kindergarten children, socioeconomic factors are found to be associated with the inequalities in caries distribution 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation